A Foresight Framework for the Labor Market with Special Reference to Managerial Roles—Toward Diversified Skill Portfolios - Anna-Maria Kanzola; Panagiotis E. Petrakis (Forecasting)
This study introduces a methodology for labor market foresight through alternative futures. It discusses three alternative scenarios for managerial roles, each exploring varying levels of technological advancement and economic growth, to provide insights into the evolving demands for managerial roles. By drafting a diversified skill portfolio, it is argued that employability skills for managers concern providing education in a combination of areas, such as new technologies, trend analysis, and strategic foresight based on the sector in which the firm operates, negotiation skills and human resources management, contemporary sales techniques, entrepreneurship, and personal growth, including time management, creativity, public speaking skills, and foresight skills. Utilizing responses obtained through an online survey administered in Greece during 2024 to managers and employing principal component analysis (PCA), we establish correlations between skill portfolio composition preferences, foresight analysis, and design of diversified skill portfolios. Diversified skill portfolios are a holistic approach to training, reskilling, and upskilling, including an optimum combination of foundational, complex, digital, green, and always case-fit per occupation or sector of economic activity. Consequently, the insights derived from this study offer a microeconomic perspective regarding the optimal combination of skills for managerial occupations and a macroeconomic perspective concerning the formulation of future training policies for human capital development.